The Relationship Between Personal Hygiene Knowledge and the Incidence of Vaginal Discharge in Adolescent Girls at MAN 3 Bogor - Adelia Cahaya, Putri; Chadaryanti, Diyah (LPPM Universitas Mohammad Husni Thamrin, 2025)
Introduction One of the simplest and most effective ways to prevent malnutrition in toddlers is by implementing a balanced nutrition pattern from an early age. Balanced nutrition plays an important role in supporting children’s growth and development, as well as enhancing their immune systems. However, many mothers of toddlers still lack understanding of the principles of balanced nutrition, including the appropriate proportions of carbohydrates, proteins, fats, vitamins, and minerals according to children’s needs. Therefore, nutrition education activities were conducted for mothers of toddlers at the Halim Perdanakusuma Posyandu. Method The activity was carried out through interactive health education sessions with mothers of toddlers at the Halim Perdanakusuma Posyandu. The materials covered principles of balanced nutrition, the importance of providing nutritious food, and the prevention of malnutrition. Evaluation was conducted using pre-test and post-test assessments to measure participants’ knowledge improvement after the educational session.Results Before the education session, most participants (10 out of 15) had moderate knowledge about balanced nutrition, and 5 participants had low knowledge. After the session, all participants (15 out of 15) demonstrated improved understanding, with post-test scores categorized as good (70–100). In addition, participants were able to mention examples of balanced menus appropriate for toddlers’ age and nutritional needs.Conclusion:Balanced nutrition education was proven effective in increasing mothers’ knowledge about the importance of applying balanced nutrition to prevent malnutrition in children. Continuous education and regular mentoring by Posyandu cadres are necessary to ensure the implementation of balanced nutrition practices in daily life. Recommendation: Regular nutrition education and comprehensive monitoring of toddlers’ nutritional status by health workers and Posyandu cadres are recommended.